Congenital disorders of glycosylation: The Saudi experience. Issue 10 (25th July 2017) - Alsubhi, Sarah; Alhashem, Amal; Faqeih, Eissa; Alfadhel, Majid; Alfaifi, Abdullah; Altuwaijri, Waleed; Alsahli, Saud; Aldhalaan, Hesham; Alkuraya, Fowzan S.; Hundallah, Khalid; Mahmoud, Adel; Alasmari, Ali; et al.
Abstract : We retrospectively reviewed Saudi patients who had a congenital disorder of glycosylation (CDG). Twenty‐seven Saudi patients (14 males, 13 females) from 13 unrelated families were identified. Based on molecular studies, the 27 CDG patients were classified into different subtypes: ALG9 ‐CDG (8 patients, 29.5%), ALG3 ‐CDG (7 patients, 26%), COG6 ‐CDG (7 patients, 26%), MGAT2 ‐CDG (3 patients, 11%), SLC35A2 ‐CDG (1 patient), and PMM2 ‐CDG (1 patient). All the patients had homozygous gene mutations. The combined carrier frequency of CDG for the encountered founder mutations in the Saudi population is 11.5 per 10, 000, which translates to a minimum disease burden of 14 patients per 1, 000, 000. Our study provides comprehensive epidemiologic information and prevalence figures for each of these CDG in a large cohort of congenital disorder of glycosylation patients.